Rapid Detection of blaKPC, blaNDM, blaOXA-48-like and blaIMP Carbapenemases in Enterobacterales Using Recombinase Polymerase Amplification Combined With Lateral Flow Strip - Wang, Fang; Wang, Lei; Chen, Huimin; Li, Na; Wang, Yan; Li, Yan; Liang, Wei (Frontiers in Cellular and Infection Microbiology, 2021)
The emergence of carbapenemase-producing Enterobacterales (CPE) infections is a major global public health threat. Rapid and accurate detection of pathogenic bacteria is essential to optimize treatment and timely avoid further transmission of these bacteria. Here, we aimed to develop a rapid on site visualization detection method for CPE using improved recombinase polymerase amplification (RPA) combined with lateral flow strip (LFS) method, based on four most popular carbapenemase genes: blaKPC, blaNDM, blaOXA-48-like, and blaIMP. All available allelic variants of the above carbapenemases were downloaded from the β-lactamase database, and the conserved regions were used as targets for RPA assay. Five primer sets were designed targeting to each carbapenemase gene and the RPA amplification products were analyzed by agarose gel electrophoresis. FITC-labeled specific probes were selected, combined with the best performance primer set (Biotin-labeled on the reverse primer), and detected by RPA-LFS. Mismatches were made to exclude the false positive signals interference. This assay was evaluated in 207 clinically validated carbapenem-resistant Enterobacterales (CRE) isolates and made a comparison with conventional PCR. Results showed that the established RPA-LFS assay for CPE could be realized within 30 min at a constant temperature of 37°C and visually detected amplification products without the need for special equipment. This assay could specifically differentiate the four classes of carbapenemases without cross-reactivity and shared a minimum detection limit of 100 fg/reaction (for blaKPC, blaNDM, and blaOXA-48-like) or 1000 fg/reaction (for blaIMP), which is ten times more sensitive than PCR. Furthermore, the detection of 207 pre-validated clinically CRE strains using the RPA-LFS method resulted in 134 blaKPC, 69 blaNDM, 3 blaOXA-48-like, and 1 blaIMP. The results of the RPA-LFS assay were in consistent with PCR, indicating that this method shared high sensitivity and specificity. Therefore, the RPA-LFS method for CPE may be a simple, specific, and sensitive method for the rapid diagnosis of carbapenemase Enterobacterales.